'We just dilute sugar and give' health workers' reports of management of paediatric hypoglycaemia in a referral hospital in Malawi. Issue 1 (1st January 2018) - Lindsjö, Cecilia; Chirambo, Chawanangwa Mahebere; Langton, Josephine; Dube, Queen; Baker, Tim; Hildenwall, Helena
ABSTRACT: Background : Acutely sick children in resource-constrained settings who present with hypoglycaemia have poor outcomes. Studies have questioned the current hypoglycaemia treatment cut-off level of 2.5 mmol/l. Improved knowledge about health workers' attitudes towards and management of hypoglycaemia is needed to understand the potential effects of a raised cut-off level. Objective : This research explored health workers' perceptions about managing acutely ill children with hypoglycaemia in a Malawian referral hospital. A secondary objective was to explore health workers' opinions about a potential increase in the hypoglycaemia cut-off level. Methods : We used a qualitative design with semi-structured individual interviews performed with health workers in the Paediatric Accident and Emergency Unit at Queen Elizabeth Central Hospital, Malawi, in October 2016. Data were analysed using latent content analysis. Ethical approval was obtained from the University of Malawi, College of Medicine Research and Ethics Committee P.01/16/1852. Results : Four themes were formed that described the responses. The first, 'Critical and difficult cases need easy treatment', showed that health workers perceived hypoglycaemia as a severe condition that was easily manageable. The second, 'Health system issues', revealed challenges relating to staffing and resource availability. The third, 'From parental reluctance to demand', described a change in parents' attitudes regarding intravenous treatments. The fourth, 'Positive about the change but need more information', exposed health workers' concerns about potential risks of a raised cut-off level for hypoglycaemia treatment, as well as benefits for the patients. Conclusions : Health workers perceived hypoglycaemia as a severe condition that is easy to manage when the required equipment and supplies are available. Due to the common lack of test equipment and dextrose supplies, health workers have adopted alternative strategies to diagnose and manage hypoglycaemia. A change to the hypoglycaemia treatment cut-off level raised concerns about potential risks, but was also thought to be of benefit for some patients.